2021
DOI: 10.3390/children8040295
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bioelectrical Impedance-Based Methods on Body Composition in Young Patients with Obesity

Abstract: (1) Background: The determination of body composition is an important method to investigate patients with obesity and to evaluate the efficacy of individualized medical interventions. Bioelectrical impedance-based methods are non-invasive and widely applied but need to be validated for their use in young patients with obesity. (2) Methods: We compiled data from three independent studies on children and adolescents with obesity, measuring body composition with two bioelectrical impedance-based devices (TANITA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Underestimation of %FM BIA compared %FM ADP in the current study is in general agreement with previous studies. 20,21,23,40 Previous studies have shown %FM BIA to be underestimated by 0.5 -5.6% in children and adolescents compared to %FM ADP ; although some %FM BIA prediction equations have resulted in an overestimation. 21 The mean underestimation of 3.4% found in the present study is within the range previously reported.…”
Section: Concurrent Validitymentioning
confidence: 99%
“…Underestimation of %FM BIA compared %FM ADP in the current study is in general agreement with previous studies. 20,21,23,40 Previous studies have shown %FM BIA to be underestimated by 0.5 -5.6% in children and adolescents compared to %FM ADP ; although some %FM BIA prediction equations have resulted in an overestimation. 21 The mean underestimation of 3.4% found in the present study is within the range previously reported.…”
Section: Concurrent Validitymentioning
confidence: 99%
“…BIA is used in many branches of medicine (Figure 3). It can be successfully used in both malnourished [22][23][24][25], and obese people [13,[16][17][18][19][20][21][22][23][24][25][26][27][28]. However, for patients with severe abdominal obesity, percentage of body fat may be overestimated [29].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this paper is to provide a review of different applications of BIA in pregnant and postpartum women. Scientific articles in the Pubmed database, Wiley It can be successfully used in both malnourished [22][23][24][25], and obese people [13,[16][17][18][19][20][21][22][23][24][25][26][27][28]. However, for patients with severe abdominal obesity, percentage of body fat may be overestimated [29].…”
Section: Introductionmentioning
confidence: 99%
“…The studies of Ofenheimer et al, Valencia-Sosa et al, and Thajer et al focused on the use and utility of certain body composition indicators in healthy or ill children [ 11 , 12 , 13 ]. In particular, Ofenheimer et al explored serum lipid profiles in relation to body composition in a large cohort of 1394 children and adolescents (6–<18 years old), who participated in the LEAD study in 2011–2019 [ 11 ].…”
mentioning
confidence: 99%
“…Thajer et al compared different methods of BIA in 123 children and adolescents (6–18 years old) with obesity in Austria [ 13 ]. More specifically, two BIA devices, namely TANITA and BIACORPUS, were used to assess body fat in all the study participants, while gold standard techniques (i.e., dual X-ray absorptiometry and air displacement plethysmography) were also applied in a subsample of volunteers.…”
mentioning
confidence: 99%